PENGARUH FIRM SIZE, LIKUIDITAS, PROFITABILITAS, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAN - Chandra; Aries Jonathan (E-Jurnal Akuntansi TSM, 2022)
The investor doing investment needs to see the value of the company owned by the company. This study aims to obtain empirical evidence and analyze the effect of firm size, liquidity, profitability, institutional ownership, dividend payout ratio, and debt to equity ratio as independent variables on firm value as dependent variable. This research uses 79 non-financial companies listed on the Indonesia Stock Exchange consistently from 2017 to 2020. Sample data were selected using purposive sampling method. This study uses multiple regression models to analyze this research data. Firm size uses natural logarithm measurements, institutional ownership uses ratio scale measurements and other variables use financial ratio measurements. The result shows that return on asset has an influence on firm value, which means that low profits with a lot of assets can make investors give negative signals that can reduce firm value. Return on equity has an influence on firm value, which means that companies that can use their equity to make profits will increase firm value. Debt to equity ratio has an influence on firm value, which means that companies that have a lot of debt will pay more interest so that it can reduce profits and firm value. Firm size, liquidity, institutional ownership, and dividend payout ratio do not have an influence on firm value